Application Of Natural Decomposition Method For Solution Of Fractional Black-Scholes Equation - Bature, Sani Sufyan; Sumiati, Ira (iora, 2023)
The Black-Scholes equation is a partial differential equation that can model the European call option price problem. This equation can be of the order of natural numbers or fractional. The aim of this paper is to find a solution to the fractional order Black-Scholes partial differential equation. The method used to find solutions to these equations is the Natural decomposition method. Two numerical examples are presented in this paper. The results show that the Natural decomposition method is effective and easy to use to solve the fractional Black-Scholes equation.